2014
DOI: 10.1371/journal.pone.0106824
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Benefit of C1-Esterase Inhibitor in Neuromyelitis Optica Evaluated In Vitro and in an Experimental Rat Model

Abstract: Neuromyelitis optica (NMO) is an autoimmune demyelinating disease of the central nervous system in which binding of anti-aquaporin-4 (AQP4) autoantibodies (NMO-IgG) to astrocytes causes complement-dependent cytotoxicity (CDC) and inflammation resulting in oligodendrocyte and neuronal injury. There is compelling evidence for a central role of complement in NMO pathogenesis. Here, we evaluated the potential of C1-esterase inhibitor (C1-inh) for complement-targeted therapy of NMO. C1-inh is an anti-inflammatory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The motivation for this work is the central importance of complement-mediated cytotoxicity in AQP4-IgG seropositive NMO, and the predicted importance, as demonstrated in experimental animal models [15, 17, 18] and by theoretical considerations [37], of complement regulator proteins in modulating complement action on target cells. Though there has been considerable research on complement mechanisms in NMO pathogenesis and on the development and testing of complement-targeted therapeutics [16, 25, 38], there has been relatively little work on complement regulator proteins in NMO. Increasing the expression or activity of complement regulator proteins on target cells is a logical extension of complement inhibitor therapy for NMO, with the potential advantage of avoiding the immunosuppressive actions of global complement inhibition and their concomitant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The motivation for this work is the central importance of complement-mediated cytotoxicity in AQP4-IgG seropositive NMO, and the predicted importance, as demonstrated in experimental animal models [15, 17, 18] and by theoretical considerations [37], of complement regulator proteins in modulating complement action on target cells. Though there has been considerable research on complement mechanisms in NMO pathogenesis and on the development and testing of complement-targeted therapeutics [16, 25, 38], there has been relatively little work on complement regulator proteins in NMO. Increasing the expression or activity of complement regulator proteins on target cells is a logical extension of complement inhibitor therapy for NMO, with the potential advantage of avoiding the immunosuppressive actions of global complement inhibition and their concomitant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nine patients recovered to their pre‐attack neurological conditions, although two required plasmapheresis as an escalation therapy. In a rat model of NMOSD, C1‐esterase inhibitor partially inhibited AQP4‐Ab‐dependent complement‐dependent cytotoxicity (CDC) in vitro , but did not inhibit serum complement activity or reduce inflammatory lesions . These findings show that further investigation is required to explore the mechanism of action of C1‐esterase inhibitor.…”
Section: Emerging Therapies For Acute Exacerbationsmentioning
confidence: 93%
“…A phase Ib clinical trial of the C1-esterase inhibitor Cinryze, which inhibits the C1 complex of the antibody-initiated classical complement pathway, was safe in humans, with no adverse events ( 123 ) (NCT01759602). However, the drug has not been studied further in NMO clinical trials, and a follow-up study in a rat model of NMO concluded that complement inhibition with this drug was too low to reduce pathology and to be of clinical benefit ( 124 ).…”
Section: Neuromyelitis Optica (Nmo)mentioning
confidence: 99%